BIOSYNTHESIS SILVER NANOPARTICLE USING FRESH WATER ALGAE - Dahlia Dahlia; Sherry Aristyani; Robiatul Hadawiyah (UNEJ e-Proceeding, 2016)
Fresh water algae such as Hydrodictyon sp.and Oedogonium sp. is common and have wide deployment in Indonesia. Unfortunately, these algae is not widely used by the people except for fish food by the people.In this study, we investigated these algae for synthesizing silver nanoparticle (AgNPs). The AgNPs were prepared by the reaction of 1 mM silver nitrate and aqueous extract of Hydrodictyon sp.and Oedogonium sp. The AgNPs were characterized by spectrophotometer and XRD. From this study, it has been concluded that fresh water algae Hydrodictyon sp.and Oedogonium sp .could be materials for producing AgNPs but it was still not perfectly.